Enhancing Students' Understanding of Local Culture through an English Curriculum: The Case of Ngada - Awe, Ermelinda Yosefa; Noge, Maria Desidaria; Anu, Theresia Irmina; Ota, Maria Kristina; Kasimo, Yulius Yosef (Universitas Pendidikan Ganesha, 2024)
The issue of the limited English curriculum that introduces local culture affects students' understanding of regional cultural wealth. This study aims to develop and analyze the quality of curriculum development products, namely the syllabus and English lesson design based on Ngada local culture. This study employs the Research and Development (R&D) method with the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. The research subjects consisted of an English teacher as content expert, high school and junior high school teachers as material experts, five elementary school teachers as product users, and two local cultural figures as local culture experts. Data were collected through expert testing, product user trials, and interviews with local cultural figures. The analysis results show that the English curriculum based on Ngada local culture is highly feasible to use. The content expert test obtained a score of 67.5 with an average of 4.45, which falls under the